2022
DOI: 10.1037/dev0001374
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of future expectations among urban adolescents in Cambodia.

Abstract: i at M anoa Adolescents are tasked with navigating competing priorities, including whether to marry, have children, pursue a job/career, go to college, and contribute to society. The developmental task of building expectations for the future is especially complex for Cambodian adolescents living within a society that strongly prioritizes family obligations yet increasingly provides educational and professional opportunities. The current study, guided by Seginer's (2003) future orientation model, applied latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…The way in which we imagine our future, given the thinking term (short or long), is influenced by our goals and desires in the present [4]. In early adulthood, the goals and desires revolve around the building of a family and the starting of a career [29], and accordingly it was found that personalfamily expectations, professional expectations, and the combination between them were dominant.…”
Section: Discussionmentioning
confidence: 99%
“…The way in which we imagine our future, given the thinking term (short or long), is influenced by our goals and desires in the present [4]. In early adulthood, the goals and desires revolve around the building of a family and the starting of a career [29], and accordingly it was found that personalfamily expectations, professional expectations, and the combination between them were dominant.…”
Section: Discussionmentioning
confidence: 99%